(untitled) - Pospisil, Jiri (e-Pedagogium, 2003)
This short pedagogical study with philosophical base concerning pansophistic and pampaedetic problems in work of John Amos Comenius and would like to show problem of understanding and definition of natural target of human in modern pedagogy.
Keywords: J. A. Comenius; pansophia; pampaedia; De rerum humanarum emendatione consultatio catholica; problems in Pampaedia